Post-ischemic environmental enrichment protects the retina from ischemic damage in adult rats - Dorfman, Damián (2013)
The aim of this study was to elucidate whether post-ischemic enriched environment (EE) housing protects the retina from ischemic damage in adult rats, and the involvement of glutamate in retinal protection induced by EE housing. For this purpose, ischemia was induced by increasing intraocular pressure to 120 mm Hg for 40 min. After ischemia, animals were housed in a standard environment (SE) or EE and subjected to electroretinography and histological analysis. EE housing afforded significant functional protection in eyes exposed to ischemia/reperfusion injury. A marked reduction in retinal thickness and ganglion cell number, and an increase in Müller cell glial fibrillary acidic protein (GFAP) levels were observed in ischemic retinas from SE-housed animals, which were reversed by EE housing. A deficit in anterograde transport from the retina to the superior colliculus was observed in SE- but not in EE-housed animals. In SE-housed animals, ischemia induced a significant decrease in retinal glutamate uptake and glutamine synthetase activity, whereas EE housing reversed the effect of ischemia on these parameters. The intravitreal injection of supraphysiological levels of glutamate partially reproduced retinal alterations induced by ischemia/reperfusion, which were abrogated by EE housing. These results indicate that EE housing significantly protected retinal function and histology from ischemia/reperfusion injury in adult rats, likely through a glutamate-dependent mechanism.